Reasons for Undesirable Pregnancy Outcomes among Women with Appendicitis: The Experience of a Tertiary Center. (15th September 2020) - Mantoglu, Baris; Altintoprak, Fatih; Firat, Necattin; Gonullu, Emre; Dikicier, Enis; Akdeniz, Yesim; Aziret, Mehmet; Erkorkmaz, Unal
Abstract : Background . Although laparoscopic appendectomy increases its popularity today, the answer to the question of whether to perform open or laparoscopic appendectomy during pregnancy is appropriate in many studies, and the choice of surgery depends on the surgeon. Herein, we aimed to evaluate the variables that affect undesirable pregnancy outcomes that occur as a result of appendicitis during pregnancy. Methods . Seventy-eight pregnant patients with acute appendicitis who underwent laparoscopic or open technique intervention enrolled in this retrospective study. In addition to the demographic structure of the patients, surgical technique, the number of pregnancies, multiple pregnancy status, surgical pathologies, laboratory values, radiological imaging methods, and length of hospital stay were evaluated. The severity of appendicitis was classified according to the pathology results. The patients were divided into two groups according to the outcomes of their pregnancy. Preterm delivery and abortion involved in the study as a single complication section. Results . The mean age of the pregnant patients was 28.6 ± 5. Of the 78 pregnant women with appendicitis, 47.4% had their first pregnancy, 37.2% had their second pregnancy, and 15.4% had 3 or more pregnancies. The preterm delivery and abortus were 19.5% in the open appendectomy (OA) group and 16.2% in the laparoscopic appendectomy (LA) group. No statistically significant difference was detected in this group in terms of appendicitis pathology triggering preterm delivery or abortion (p 0.075). When white blood count (WBC) and C-reactive protein (CRP) were evaluated by laboratory findings, CRP was found to be statistically significantly higher in patients with preterm birth (p 0.042). Conclusion . Consequently, acute appendicitis may cause serious intra-abdominal infection and inflammation in addition to the complexity of the diagnosis due to the nature of pregnancy, as well as undesired pregnancy outcomes with the surgical technique, or independently with other variables.